2016
DOI: 10.1016/j.cell.2016.03.020
|View full text |Cite|
|
Sign up to set email alerts
|

Oncogenic Role of Fusion-circRNAs Derived from Cancer-Associated Chromosomal Translocations

Abstract: Chromosomal translocations encode oncogenic fusion proteins that have been proven to be causally involved in tumorigenesis. Our understanding of whether such genomic alterations also affect non-coding RNAs is limited, and their impact on circular RNAs (circRNAs) has not been explored. Here, we show that well-established cancer-associated chromosomal translocations give rise to fusion circRNAs (f-circRNA) that are produced from transcribed exons of distinct genes affected by the translocations. F-circRNAs contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
520
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 589 publications
(527 citation statements)
references
References 53 publications
4
520
0
3
Order By: Relevance
“…16,29,30 Moreover, some potentially unique circRNAs (such as f-circRNAs) were found to be expressed only in pathological conditions. 27 For example, a circRNA named circ_101222 was found to be more significantly enriched in the blood corpuscles of patients with pre-eclampsia than in those of corresponding healthy controls. 54 Using the plasma protein factor endoglin (ENG) in combination with circ_101222 resulted in a sensitivity of 0.7073, a specificity of 0.8049, and overall area under the curve of 0.876 (95% confidence interval 0.816-0.922) for the prediction of pre-eclampsia.…”
Section: Clinical Implication Of Human Circrnasmentioning
confidence: 99%
See 2 more Smart Citations
“…16,29,30 Moreover, some potentially unique circRNAs (such as f-circRNAs) were found to be expressed only in pathological conditions. 27 For example, a circRNA named circ_101222 was found to be more significantly enriched in the blood corpuscles of patients with pre-eclampsia than in those of corresponding healthy controls. 54 Using the plasma protein factor endoglin (ENG) in combination with circ_101222 resulted in a sensitivity of 0.7073, a specificity of 0.8049, and overall area under the curve of 0.876 (95% confidence interval 0.816-0.922) for the prediction of pre-eclampsia.…”
Section: Clinical Implication Of Human Circrnasmentioning
confidence: 99%
“…Because the expression of f-circRNAs in cancer cells is essential for their maintenance and confers resistance to chemotherapy, it has been suggested that pharmaceutical interventions that are aimed at blocking f-circRNAs or their down-stream effectors could prove to be beneficial as therapeutic targets to eradicate diseases. 27 Another study that employed in vivo delivery of siRNA-targeting endogenous circ-Foxo3 showed that it abrogated the effect of doxorubicin-induced cardiomyopathy, suggesting a potential therapeutic approach for myocardial protection. 25 …”
Section: Clinical Implication Of Human Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Guarnerio and colleagues revealed that the PML/RARa translocation in acute promyelocytic leukemia (APL), MLL/ AF9 translocation in acute myeloid leukemia (AML), EWSR1/ FL1 translocation in Ewing sarcoma, and EML4/ALK1 translocation in lung cancer all generate aberrant circular RNAs via this mechanism. 78 These fusion circular RNAs, which are not expressed in normal cells, promote cancer development in part by contributing to cellular transformation and protecting cancer cells from drug-induced apoptosis. Circular RNAs may thus represent promising new therapeutic targets.…”
Section: Translocations Shuffle Intronic Repeats To Cause Aberrant CImentioning
confidence: 99%
“…Second, many circRNAs have been linked to cancer development and progression. Notably, aberrant circRNAs have been also identified in cancer as proto-tumorigenic products of chromosomal translocations [11]. Thus, the opposite outcome, in terms of gene expression, that is observed in acute vs chronic targeting of Cdr1as could have tremendous therapeutic implications, and it will be critical to test multiple treatment strategies in pre-clinical settings (e.g., metronomic vs continuous administration of the RNA medicine of interest) (Figure 1).…”
mentioning
confidence: 99%